Distillation, Characterizations, and Testing of Distillation Products from Waste Lubricant Oil (WLO) using Compression-Ignition Engine - Sugeng Priyanto; Ahmad Lubi; Ferry Budhi Susetyo; Danar Hari Krisyono; Sigit Dwi Yudanto; Fakhrony Sholahudin Rohman; Sudibyo Sudibyo (Automotive Experiences, 2024)
Waste lubricant oil is always found in motor vehicle repair shops. Utilizing waste lubricant oil by distilling it will provide benefits. For this reason, waste lubricant oil was distilled in this research. Several characterizations were conducted to determine the viscosity, density, low heat value (LHV), and flash point of waste lubricant oil and distillation products. The distillation product is less viscous, denser, LHV, and flash point than lubricant oil waste. The distillation product was mixed with Pertamina DEX (0, 5, 10, and 15 vol.%) and then filled into the fuel tank for the engine performance test. The present experiment utilized a compression-ignition (CI) engine to measure performance. CI engine speed variations were carried out at 1000, 1500, 2000, and 2500 to see the influence of the mixed fuel on torque, power, specific fuel consumption (SFC), thermal efficiency, and smoke opacity. The increase in CI engine speed leads to an increase in torque, power, thermal efficiency, and smoke opacity, but at the same time, SFC decreases to 2500 rpm. Increasing the distillation product content in the mixed fuel decreased torque, power, SFC, thermal efficiency, and increased smoke opacity.